Some aspects of the geochemistry of gallium in silicate rocks and stony meteorites - Willis, James P (Department of Geological Sciences, 2016)
The objects of the work presented here were: to develop an accurate method for the determination of gallium on a routine basis in rocks and meteorites at concentrations down to or less than 1 ppm Ga with a precision (c.o.v.) at the 10 ppm level and above of 1-2% (1s); to apply this technique to the determination of Ga in rocks and meteorites; by critically examining the high quality data thus obtained, to compare the distribution of gallium in various meteorite types, as well as in igneous, sedimentary and metamorphic rocks, seeking to define, where possible, the fine structure of its distribution and its relationship with aluminium during geological processes; and to evaluate the possibility of using variations in the gallium contents and Ga/Al ratios of rocks both to assist in the interpretation of the geochemical history of differentiated suites and to define regional differences, as has been done with other trace elements. Bibliography: pages 219-247.